Public trust in physicians: empirical analysis of patient-related factors affecting trust in physicians in China - Changle Li; M. Mahmud Khan (BMC Primary Care, 2022)
Abstract Background Trust between the parties is essential for the efficient functioning of the healthcare market. Physician-patient relationship represents an asymmetric information situation and trust in physicians is critical for improving health and wellbeing of patients. In China, trust in physicians appears to be quite low creating conflicts between physicians and patients. This study aims to identify some general factors associated with trust in physicians in general using a nationally representative survey. Methods A cross-sectional analysis using data from 2018 China Family Panel Study (CFPS). Survey responses of individuals aged 16 years or above were extracted from CFPS and the final sample consisted of 29,192 individuals. An ordered probit model was used to identify factors causing heterogeneity in the levels of trust in physicians. Results Higher educational attainment and having medical insurance coverage are associated with higher likelihood of trusting physicians. Older adults (> = 30 years), males, urban residents, wage-earners, and self-employed persons are less likely to trust physicians. People who are diagnosed as chronic diseases or current smokers indicate lower level of trust in physicians. Higher perceived quality of services improves trust. Conclusion Socioeconomically disadvantaged population groups and uninsured individuals are less likely to trust physicians. Health care delivery system needs to address the concerns of these specific population groups to reduce tensions between physicians and patients. Increasing health insurance coverage and offering insurance with low out-of-pocket expenses should reduce the perception that physicians are more guided by their income rather than the wellbeing of patients. The system should also develop a comprehensive bill of rights of patients to improve patient-physician relationship.